HUBUNGAN PERAN TEMAN SEBAYA DAN DUKUNGAN KELUARGA DENGAN PERILAKU KENAKALAN REMAJA DI SMP NEGERI 92 JAKARTA - Leni Marlia (2020)
Juvenile delinquency is unlawful or illegal behavior committed by adolescents as a result of the social neglect. The forms of delinquency in this study were truancy, smoking, bullying, fighting, and disobedience to parents. Delinquency committed by adolescents is caused by various things. This study wanted to found out the correlation between the role of peers and family support with juvenile delinquency behavior at 92 Junior High School Jakarta. This study used quantitative research with cross sectional design and chi square test to analyzed the correlation between variables. This study used simple random sampling technique with 140 respondents taken from class VIII. The results showed the correlation role of peers and family support with juvenile delinquency behavior each had a p-value of 0,000 and 0.004. The conclusion in this study there were a significant correlation between the role of peers and family support with juvenile delinquency behavior. The school were expected to provide counseling and guidance so that adolescents not engaged with delinquency.